(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To identify the similarity of lower urinary tract symptoms presented in the urodynamic study compared to the urinary diary. Method: This is a comparative study carried out in an urodynamics clinic in southern Santa Catarina, Brazil, with 44 patients who underwent the examination. Data collection was carried out by applying a questionnaire and a 72-hour bladder diary and comparing it with the findings of the urodynamic study using the SPSS for Windows and Stata/SE v.14.1 programs. Results: The bladder diary showed high specificity, sensitivity, and accuracy for identifying detrusor hyperactivity and stress urinary incontinence. There was no difference for bladder capacity (p* 0.198). It pointed to bladder sensitivity with a volume smaller than that presented by the urodynamic study (p*<0.001). It was able to identify lower urinary tract symptoms that were not present in the urodynamic study. Conclusion: The bladder diary was effective for identifying lower urinary tract symptoms and can be used to define first-line treatment with a broader range of population diagnosis, shorter time between complaints and treatment, cost reduction for the system, and less discomfort for the patient.